Metformin carbon dots enhance neurogenesis and neuroprotection in Alzheimer's disease: A potential nanomedicine approach - Jing Zhang; Xuehan Yang; Sushan Wang; Jianhua Dong; Meishuang Zhang; Ming Zhang; Li Chen (Materials Today Bio)
Alzheimer's disease (AD) is characterized by progressive cognitive decline due to neuronal damage and impaired neurogenesis. Preserving neuronal integrity and stimulating neurogenesis are promising therapeutic strategies to combat AD-related cognitive dysfunction. In this study, we synthesized metformin carbon dots (CMCDs) using a hydrothermal method with metformin hydrochloride and citric acid as precursors. Notably, we found that CMCDs were significantly more effective than metformin in promoting the differentiation of neural stem cells (NSCs) into functional neurons under amyloid-beta (Aβ) conditions. Moreover, CMCDs fostered NSCs proliferation, enhanced neurogenesis, reduced Aβ deposition, and inhibited glial cell activation. We also examined neuronal structure by assessing Map2/NF-H/PSD95/SYN expression in the hippocampus, finding that CMCDs robustly strengthened neuronal structure. These results suggest that CMCDs can cognitive dysfunction in AD and promote the proliferation and neurogenesis of NSCs, as well as ameliorate neuronal injury. Hence, CMCDs emerge as promising candidates for AD therapy, demonstrating superior efficacy compared to metformin alone, and offering novel insights into small molecule drug interventions for AD.